Intraductal Papillary Mucinous Neoplasms of the Pancreas: Clinical Surveillance and Malignant Progression, Multifocality and Implications of a Field-Defect - Remotti, Helen Elaine; Winner, Megan; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Intraductal papillary mucinous neoplasms (IPMNs) are a heterogeneous group of mucin producing cystic tumors that involve the main pancreatic duct and/or branch ducts and may be associated with invasive carcinoma. Predicting the risk of malignant transformation of an IPMN lesion can be challenging. The Sendai criteria, based in large part on radiographic imaging features, help guide surgical intervention based on the stratification of cysts into high and low risk lesions for malignancy. Invasive carcinoma may develop in the index IPMN lesion or in a separate site within the pancreas, supporting the concept of a field defect in IPMN tumorigenesis. This stresses the importance of evaluation of the entire pancreas upon diagnosis of IPMN and continued surveillance of the residual pancreas following resection. Herein, the authors summarize the data presented at the 2012 ASCO Gastrointestinal Cancers Symposium regarding prevalence and site of invasive carcinoma detected in patients undergoing surveillance for IPMN (Abstract #152).